So far, so close. Prehistoric studies and digital technologies in a changing environment - Palombini, Augusto; Gioia, Patrizia; Peretto, Carlo; Zullo, Enza (Journal of Mediterranean Earth Sciences, 2023)
The relationship of prehistoric science with digital technologies and methods seems to be more complex than it has been for other branches of archaeology. Analyzing three Italian case studies (the 1985 exhibition “Homo, viaggio alle origini della storia”, the Casal de’ Pazzi Museum, and the Palaeolithic Museum of “La Pineta”), the authors trace a reflection on the way the Western culture dealt with the representation of human most ancient past and try to look forward at possible future evolution and applications of this field of study.